Embolization of congenital hemangioma with severe hemorrhage - Masafumi Kamata; Noriko Aramaki-Hattori; Keisuke Okabe; Shigeki Sakai; Seishi Nakatsuka; Masahiro Jinzaki; Kazuo Kishi; Masanori Inoue (Elsevier, 2021)
Congenital hemangioma is a rare vascular lesion in children. Although most cases are asymptomatic, severe complications can arise, including severe bleeding. We describe the case of a female infant who was born with a congenital hemangioma on her right thigh. Ulceration appeared at the center of the tumor and gradually progressed over the following weeks. One month after birth, the lesion started hemorrhaging severely. Transfusions were required. The bleeding recurred repeatedly despite compression therapy. Embolization was performed urgently and succeeded in arresting the hemorrhage. Bleeding did not recur and the lesion involuted completely over the next few months. A literature review revealed that this is the eighth case where embolization was used to arrest severe hemorrhage of a congenital hemangioma. In the previous cases, embolization permanently (five cases) or temporarily (two cases) arrested the bleeding. In one of the latter cases, selective hemostatic surgery successfully arrested bleeding recurrence after embolization. In the other, the patient had Von Willebrand's Disease; while embolization arrested the hemorrhaging for several years, it restarted at the age of 18 years and the lesion had to be resected to manage the bleeding. Thus, embolization can be a first choice to arrest massive bleeding of congenital hemangioma.